Bioequivalence of Two Formulations of Escitalopram - Almeida, S.; Pedroso, P.; Filipe, A.; Neves, R. I.; Tanguay, M.; Torns, A. (Arzneimittelforschung, 2012)
Escitalopram, CAS registry number 128196-01-0 is an orally administrated selective serotonin reuptake inhibitor (SSRI).The objective of this trial was to assess bioequivalence between an escitalopram formulation manufactured by Grupo Tecnimede and that of a European reference formulation, while evaluating both formulations’ tolerability as a secondary objective.24 healthy subjects were enrolled in a single centre, randomised, single-dose, open-label, 2-way crossover study. Drug levels were determined by reverse liquid chromatography and detected by tandem mass spectrometry detection, LC-MS/MS method. Pharmacokinetic parameters used for bioequivalence assessment were determined from the drug concentration data using non-compartmental analysis.Mean±Standard deviation (SD) Cmax values were 18.89±5.06 ng/mL and 18.45±5.05 ng/mL for reference and test, respectively. AUClast was 577.16±196.20 ng · h/mL after the administration of the reference and 577.69±220.88 ng · h/mL for the test. AUCinf was 595.66±203.80 ng · h/mL after the administration of the reference 596.19±235.47 ng · h/mL for the test.The 90% confidence intervals obtained by analysis of variance were 92.38–103.38% for Cmax, 94.10–104.37% for AUClast and 93.80–104.09% for AUCinf, which were within the predefined acceptable range of 80.00–125.00%. Both formulations were well tolerated, with no major side effects and no relevant differences in safety profiles observed between the preparations.The design of the study was adequate to determine the pharmacokinetic parameters of the test and the reference formulations. Bioequivalence between formulations was concluded both in terms of rate and extent of absorption.
Keywords: escitalopram; bioequivalence; AUC; Cmax; CAS number 128196-01-0